Efektifitas Cognitive Behaviour Therapy di Sekolah: Meta Analisis Review - Richma Hidayati; Nur Hidayah; M. Ramli; Imam Hambali; Triyono Triyono (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
Cognitive behavioral therapy (CBT) is a popular therapy that is applied to various problems. The purpose of this study is to provide a survey approved by a meta-analysis supported by CBT. This study reviews 10 meta-analytic studies and discusses CBT in students in schools for the following problems, namely: Anxiety, Emotion, Self-Confidence, Self-Efficacy, and CBT Based on Local Wisdom. Additional analytical meta review to address CBT problems for various problems in school children. The strongest support for CBT is from monitoring and transition. CBT showed a higher response rate and was widely considered in these 7 reviews and only three reviews reported that CBT had a lower response rate in care. In general, the CBT evidence base is very strong. However, additional research is needed to study the efficacy of CBT for randomized controlled studies. In addition, using CBT in schools depends on the level of education and age of children.